CONTINUOUS BENEFIT AND SOCIAL RIGHTS: AN ANALYSIS OF THE HISTORICAL EVOLUTION AND CRITERIA FOR GRANTING IT TO PEOPLE WITH DISABILITIES - Coelho, Adilson Manoel; de Oliveira, Jane Karla; Lustosa, Thalita Feitosa Mascarenhas; do Rego, Elson Jose (Seven Editora, 2025)
This study aims to better understand the Continuous Cash Benefit (BPC), exploring what it means, how it emerged and evolved over time, and what is its role within the set of social rights guaranteed to citizens. The main objective is to analyze the legal criteria and doctrinal understandings that support its granting, highlighting the transformations in the legislation and, above all, the centrality of human dignity in this process. This work was structured in three sections, each with a specific objective. In the first, we sought to understand what social rights are and how they have evolved over time, with emphasis on the Continuous Cash Benefit (BPC). The second section is dedicated to reflecting on the dignity of the human person and his intimate relationship with social assistance. In the third, the rules in force and the criteria used for granting the BPC are analyzed, considering both the legal and conceptual aspects involved. The methodology used was qualitative in nature, based on secondary data extracted from official sources and specialized bibliography. The results reveal that there are still important obstacles in accessing the BPC, many of them resulting from restrictive interpretations of the legislation. In addition, the urgency of a broader biopsychosocial assessment is highlighted, which goes beyond the work capacity of people with disabilities and also takes into account the social and environmental factors that directly influence their quality of life.DOI: https://doi.org/10.56238/sevened2025.018-009